Generalized R-Based and S-Based Taxes Under Uncertainty. - Bond, S; Devereux, M (Elsevier, 2003)
This paper considers the relationship between two general neutral business tax structures, which we label the "firm tax" and the "shareholder tax." The well-known R-based and S-based cash flow taxes, analysed by, are special cases of these two taxes. We demonstrate the neutrality of both taxes in the presence of uncertainty, and characterise the tax rules required in the event of default and wind-up. Our analysis provides the first proof of the neutrality of the S-based cash flow tax and the Allowance for Corporate Equity (ACE) corporation tax under uncertainty. We also discuss implementation and tax avoidance issues.